Effects of analytical and experiential self-focus on stress-induced cognitive reactivity in eating disorder psychopathology - Rawal, A; Williams, J; Park, R (2011)
Previous research suggests distinct modes of self-focus, each with distinct functional properties: Analytical self-focus appears maladaptive, with experiential self-focus having more adaptive effects on indices of cognitive-affective functioning (e.g., Watkins, Moberly, and Moulds, 2008). The authors applied this framework to eating disorder (ED) psychopathology and manipulated the mode of self-focus prior to exposure to a stressor (imagining eating a large meal; Shafran, Teachman, Kerry, and Rachman, 1999). Study 1 showed that students high in ED psychopathology reported lower post-stressor feelings of weight or shape change and less subsequent attempts to neutralise (e.g., imagining exercising) after experiential relative to analytical self-focus. Study 2 found that partially weight restored patients with anorexia nervosa had lower post-stressor estimates of their own weight and reported lower urge to cancel stressor effects following experiential compared to analytical self-focus. Experiential self-focus was also followed by less neutralisation than analytical self-focus. Results suggest that the mode of self-focus affects cognitive reactivity following a stressor in individuals with ED psychopathology. Examining the mode within which individuals with ED psychopathology focus on self and body may raise important implications for understanding of psychopathology and open new possibilities for augmenting current treatments. © 2011 Elsevier Ltd.